Educating the neglected majority : the struggle for agricultural and technical education in nineteenth-century Ontario and Quebec - Jarrell, Richard A., 1946- (McGill-Queen's University Press, 2016)
"This is a comparative study of the evolution of technical and agricultural education from the early nineteenth century up to about 1900 in Ontario and Quebec. In the extensive literature on Canadian educational history, these two areas have remained largely on the periphery. No detailed picture exists of the early attempts to teach workers to fit into a Canadian society shaped by the Industrial Revolution. The provincial systems taught basic literacy to children, but did not offer specialized or adult education. Instead, technical education, under a variety of names and guises, occupied the thoughts of educational reformers, educators, legislators, manufacturers, etc., not to mention the 'mechanics' or 'artisans' who might receive it. The book describes both formal training (specialist schools, night classes, teacher training in science and art) and informal means of educating (public lectures, journalism, societies, exhibitions, etc.). The focus is upon the rural and industrial populations, rather than on middle-class-oriented professional and commercial education. The state was central to these efforts, both formal and informal, throughout the century. Earlier studies of specific aspects of education have often ignored events and ideas outside a particular region or group; Jarrell emphasizes the wider context underlying ideas about agricultural and technical education (British, French, American, Irish) and underscores the interplay between the two provinces."--